Pemanfaatan Internet of Things (IoT) Untuk Sistem Kendali dan Otomatisasi Pemeliharaan Bibit Ikan Lele - Kaffi, Muhammad Syahrul; Hidayati, Rahmi; Suhardi, Suhardi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Catfish farming is one of the fisheries businesses that requires intensive attention to various environmental factors such as water quality, weather conditions, and feeding schedules so that productivity remains optimal. These conditions if not managed properly can cause a decrease in water quality which results in fish death or growth that is not maximized. To overcome these problems, an automatic control system based on the Internet of Things (IoT) was developed by utilizing the Arduino Uno microcontroller and ESP32 as the main components in the system. The system is equipped with various sensors, such as a pH sensor to monitor water acidity, an ultrasonic sensor to measure water depth, and a rain sensor to detect weather changes. In addition, the system is also equipped with relays, water pumps, and servos that function to regulate water conditions, automatic feeding, and automatic roof operations on fish ponds. This research was tested 72 times with different values of pH and ultrasonic sensor accuracy. The test results show that this system works without errors, with the pH sensor accuracy level reaching 89% and the ultrasonic sensor at 97%. With this automation system, it is hoped that catfish farmers can manage ponds more efficiently, monitor pond conditions in real-time, and increase cultivation productivity through the management of fish ponds.